Estudo dos efeitos da adição de TiO2 e V2O5 nas propriedades dielétricas da matriz cerâmica Na2Nb4O11 (NN00) e suas aplicações em ressoadores dielétricos - Romeu, Mairton Cavalcante (2014)
In this study were investigated the structural and dielectric properties of the ferroelectric ceramic monoclinic phase Na 2 Nb 4 O 11 with the addition of titanium dioxide (TiO 2 ) and vanadium pentoxide (V 2 O 5 ) in proportions of 2, 5 and 10% by weight . The Na 2 Nb 4 O 11 powders were produced by the co nventional solid state reaction. After calcination , the samples were pressed into cylindrical pellets and then sintered. The study of the structure and composition of the samples was done by X - ray diffract ion and refinement Rieteveld and the morphology study was performed by Scanning Electron Microscopy . The density measurements we re obtained by pycnometry. The dielectric characterization was performed in the range of frequencies radio and microwave . In both cases , a study was performed of the properties with temperature variation for possible application in devices that oper ate in Frequency Radio and Microwave . The main objective of this work was to obtain ceramic dielectric resonators with high dielectric permittivity, low dielec tric loss and thermal stability , because these properties are required for applications in diele ctric filters and antennas. In the measurements performed at room temperature of 25 ° C, was obtained a high value of the dielectric permittivity ( ε'r = 129.29 ) with NN2V ( 2 % V2O5 ) and a value of loss tangent , relatively low (tan δ = 3.25x10 - 2 ) at 1 MHz. At the temperature of 400 ° C and a fixed frequency of 1 MHz was obtained a high value of the dielectric permittivity with ε' r = 358.23 and a value of dielectric loss around 3.49 x10 - 1 for sample NN2Ti. The measurement of temperature coefficient of resonance frequency ( τ f ) revealed the possibility of achieving the thermal stability ( τ f =0) with increasing level of addition of V 2 O 5 . For NN00 s ample, obtained a τ f = - 3378.42 ppm / ° C. With the addition of V2O5, this value gets closer to zero and reaches τ f = - 1348.618 ppm / ° C for NN10V. The measurements in the microwave range was obtained using the Hakki - Coleman method. A numerical simulation was performed with each sample, checking for reciprocity with the experimental data. In this study was obtained a ceramic NN10V, useful for application in low - gain omnidirectional antennas devices